Case Report: Whispers of the serpent: exploring uncommon imaging features in primary hepatic malignant mesothelioma - Li, Guoan; Hong, Shengqian; He, Tao; Xu, Jianbo (Frontiers in Medicine, 2025)
Primary hepatic malignant mesothelioma (PHMM) is an uncommon and aggressive neoplasm with vague clinical and radiological features, posing challenges for preoperative diagnosis. In our case, a lobulated hepatic mass demonstrated a serpiginous peripheral enhancement pattern on contrast-enhanced CT and MRI. This uncommon imaging manifestation has been sporadically documented in previous reports. By consolidating these findings, our report emphasizes serpiginous peripheral enhancement as a potential diagnostic clue for PHMM. Recognition of this pattern may aid earlier detection, improve differential diagnosis, and guide timely surgical decision-making in affected patients.